How WTO commitments tame uncertainty - Adam Jakubik; Roberta Piermartini (World Trade Organization (WTO), 2019)
This paper studies how WTO rules and flexibilities shape its members' trade policy responses to import shocks. Guided by a cost benefit analysis model and using a unique database of tariff bindings for all WTO countries over the 1996-2011 period, we show that WTO commitments affect members' trade policy. More stringent bindings reduce the likelihood of responding to import shocks by raising tariffs and increase the likelihood of contingent measures. We argue that this reduces overall trade policy uncertainty. In a counterfactual scenario where WTO members can arbitrarily increase tariffs they are 4.5 times more likely to do so than under current bindings.
Keywords: F13; F14; F53; 330; trade agreements; trade policy; trade policy uncertainty; anti-dumping